Peer tutoring analysis in inclusive classes using character education approach - Johana Manubey; John Rafafy Batlolona; Marleny Leasa (Intelektual Pustaka Media Utama, 2021)
This study aimed to analyze peer tutoring in inclusive classes with character education approaches for elementary students. The target of this study were 30 teachers, 525 students, and 98 disabled students from nine elementary schools in East Sumba Regency. This research focused on changing the character of students with special needs or not using peer tutoring methods that are modified with various learning techniques. The results showed a change in the character of students with special needs and not with the peer tutoring method. Thus, peer tutoring can be recommended in improving learning skills and forming student character. Future studies are expected to show how peer tutoring shapes students' emotional intelligence in inclusive classes.